Secondary metabolism as an expression of microbial growth and development - Calam, C T (Folia microbiologica, 1979)
A case is made out for regarding secondary metabolism as part of normal cell growth, related to its interactions with the environment. Secondary metabolism is widespread, especially in fungi and actinomycetes, and is not to be regarded as confined to the production of antibiotics and other special substances. It is part of the normal maturation process. Examples are given of the influence of secondary metabolism in ecological systems. It is also shown that cell productivity can be related to age structure. Secondary metabolism is thus linked with growth, although in many cases this may not be obvious in laboratory work. Initiation of production will arise from the system which regulates growth and differentiation. These processes are little understood at present, but it is clear that the factors involved differ in different instances and that they involve a very great variety of biochemical and physiological processes.
Keywords: Plants; Actinomycetales; houby; Penicillins; peniciliny; Bacteria; ekologie; Fungi; rostliny; Ecology